Pendampingan Praktek Wudhu dalam Meningkatkan Kemampuan Berwudhu di TPQ Al Husnan Desa Sidoharjo Kecamatan Pulung - Wilda Musta’idatul Walida Ismani; Medina Nur Asyifa Purnama (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article explains the pattern of ablution practice which is a problem for many children at TPQ Al Husnan, Sidoharjo Village. Assistance in the practice of ablution is very important to teach, because ablution is a method of purification and is also a valid requirement for prayer. This assistance aims to teach children to understand more about how to do ablution properly and correctly. The object or target in this assistance is the children of TPQ Al-Husnan, Sidoharjo Village, Pulung Ponorogo sub-district. The method used in this mentoring activity is ABCD (Asset Based Community Development). In carrying out this assistance, which is carried out every one week 2 times for one month. This mentoring activity is carried out because most children understand ablution only from theory, while in practice most of them are not suitable so that this problem really requires attention, namely in the form of learning assistance that remembers more about the importance of ablution for us Muslims. The result of this assistance is that children understand more about how to do ablution properly and correctly, as can be seen from the difference between the children's ablution before receiving assistance and afterwards, which is much better. This mentoring activity received a warm response from Asatidzat as well as the guardians of TPQ Al-Husnan students as well as in the implementation the children were very active and enthusiastic about participating in learning activities so that they showed a change for the better from the previous practice of ablution.